Therapeutic Strategies for Dystrophin Replacement in Duchenne Muscular Dystrophy - Happi Mbakam, Cedric; Lamothe, Gabriel; Tremblay, Jacques P. (Frontiers in Medicine, 2022)
Duchenne muscular dystrophy (DMD) is an X-linked hereditary disease characterized by progressive muscle wasting due to modifications in the DMD gene (exon deletions, nonsense mutations, intra-exonic insertions or deletions, exon duplications, splice site defects, and deep intronic mutations) that result in a lack of functional dystrophin expression. Many therapeutic approaches have so far been attempted to induce dystrophin expression and improve the patient phenotype. In this manuscript, we describe the relevant updates for some therapeutic strategies for DMD aiming to restore dystrophin expression. We also present and analyse in vitro and in vivo ongoing experimental approaches to treat the disease.